Police Revealed a Case of Necrophilia in Dhaka, Bangladesh – Legal and Psychiatric Issues - Nurunnabi, Abu Sadat Mohammad; Sultan, Mohammad Tipu; Islam, Md Mozaharul; Kayum Shaikh, Muhammad Abdul (Community Based Medical Journal, 2022)
In November 2020, the Criminal Investigation Department of Bangladesh Police revealed in front of the media that a 20-year old young male allegedly had intercourse with female cadavers under postmortem examination inside the mortuary while working as an assistant to the official mortuary attendant in a medical college in Dhaka, Bangladesh. The subject of sex is still a taboo in the country, and an offence as bizarre as necrophilia is even beyond the imaginative capacity of majority of the population. However, this case of necrophilia has stirred the sentiment of the people and at the same time thrown challenges to the legislation and forensic psychiatry service of the country that we would like to focus on. There exists no penal provision in the country which criminalizes such “particular act of necrophilia”. However, we are interested to observe the consequences. Besides, no information was made available on psychiatric evaluation of the offender while arresting and sending him to the jail. We recommend strengthening of forensic psychiatry as a discipline to operate psychiatric evaluation in such cases which is crucial for legal proceedings. Moreover, making amendments to the existing laws should be considered to encompass this type of offence. CBMJ 2021 January: vol. 10 no. 02 P: 111-114